Update on Nonsurgical, Ultraconservative Approaches to Treat Effectively Non-Cavitated Caries Lesions in Permanent Teeth - Borges, Boniek Castillo Dutra; Borges, Juliane de Souza; Araujo, Larissa Sgarbosa Napoleao de; Machado, Claudia Tavares; Santos, Alex Jose Souza dos; Pinheiro, Isauremi Vieira de Assunçao (European Journal of Dentistry, 2011)
Dental caries on tooth surfaces is still a problem in many industrialized countries. For many years, dentistry was influenced by a mechanical approach characterized by the use of high-speed rotary cutting instruments, and dentists predominantly used surgical methods to address caries. This included radical removal of diseased portions of the tooth, along with material-driven geometric extensions to areas that were assumed to be caries-resistant. This concept of extension for prevention was introduced by G. V. Black and influenced dentists for more than 120 years. Recently, a new paradigm of operative conservatism, sometimes referred to as “minimally invasive dentistry,” has gained popularity. This paradigm is designed to promote maximum preservation of healthy dental structures over a lifetime. The aim of this review is to discuss the efficacy of current nonsurgical treatments for non-cavitated caries lesions in permanent teeth. Based on results obtained from clinical trials, this review evaluates treatments such as consumption of CPP-ACP added gums, resin infiltration and fissure sealing. Although in a few cases an invasive approach is needed to arrest caries progression, the non-surgical approach generally provides potential benefits that include conserving structure by delaying intervention or minimizing the operative procedure. All current non-invasive methods are effective in treating non-cavitated caries lesions. The adoption of non-invasive approaches in the management of these lesions can preserve dental tissues, thus increasing tooth longevity. (Eur J Dent 2011;5:229-236)
Keywords: Dental history; Minimally invasive dentistry; Operative dentistry; Pit-and fissure sealants; Remineralization; Resin infiltration